Peran Kepemimpinan Kepala Sekolah dalam Mengembangkan Budaya Mutu Sekolah - Ismawiyah, Ismawiyah; Anshari, Muhammad Zulkifli; Aslamiah, Aslamiah; Cinantya, Celia; Azizah, Fitria (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2024)
Quality is the level of conformity of a product, service or work result based on standards that have been created. Quality can also be measured based on the ability of a product or service to meet the needs and expectations of users or consumers. Schools as educational service providers must guarantee quality on an ongoing basis. This needs to be supported by the formation of a quality culture in schools. A school quality culture is an important foundation in efforts to continuously improve the quality of education. In the educational context, a culture of quality includes a commitment to high standards in the teaching and learning process, school management, and achieving optimal results for all students. The principal as the main leader in the school has a very strategic role in building and developing this quality culture. The purpose of this writing is to describe the role of the principal in developing a quality culture in the school. This research method is a qualitative research method, data mining is carried out by reviewing literature (scientific articles, books and other supporting sources). The results of this research illustrate that a culture of quality can be built by optimizing the role of the school principal to the maximum, such as the role of the school as a leader. Apart from that, it also makes supervision more effective in the performance of teaching and educational staff.